Associations between serum biomarkers and non-alcoholic liver disease: Results of a clinical study of Mediterranean patients with obesity - De Nucci, Sara; Castellana, Fabio; Zupo, Roberta; Lampignano, Luisa; Di Chito, Martina; Rinaldi, Roberta; Giannuzzi, Vito; Cozzolongo, Raffaele; Piazzolla, Giuseppina; Giannelli, Gianluigi; Sardone, Rodolfo; De Pergola, Giovanni (Frontiers in Nutrition, 2022)
Background: Transient elastography is an ultrasound-based method to detect nonalcoholic fatty liver disease (NAFLD). Despite the simultaneously rising prevalence of fatty liver and metabolic disease, further information about metabolic risk indicators of fatty liver is still necessary. Methods: A Southern Italian population sample with obesity (N= 87) was cross-sectionally explored for associations among the presence of NAFLD, assessed by FibroScan, and clinical, biochemical and anthropometric parameters. Inclusion criteria were age >18 years, BMI ≥25 kg/m2, no ongoing supplemental or drug therapy, including oral contraceptives or osteoporosis medications; exclusion criteria were pregnancy, endocrinological diseases, cardiovascular diseases, neoplasia, renal or hepatic failure, hereditary thrombocytopenia, hepatitis B (HBV) or hepatitis C virus (HCV) infection, and excess alcohol consumption. Results: The study sample featured a female predominance (67%, N=60), age range 18-64 years, and 40% prevalence of NAFLD, in accordance with the fibroscan-measured controlled attenuation parameter (CAP) threshold value above 302 dB/m. Males were slightly more frequently affected by NAFLD (51.4% versus 48.6%, p=0.01). Insulin levels, insulin resistance (quantified by HOMA-IR), diastolic blood pressure, BMI, visceral adipose tissue (VAT), and waist circumference were significantly higher in the NAFLD subset compared to their counterparts (p<0.01, p<0.01, p=0.05, p<0.01, p<0.01, p<0.01 respectively). Uric acid (p<0.01) also showed a positive trend in the NAFLD group. Other liver steatosis parameters, measured by stiffness (p<0.01), fatty liver index (FLI) (p<0.01) and FibroScan-AST (FAST) (p<0.01), were also significantly greater in the NAFLD group. In three nested linear regression models built to assess associations between CAP values and serum uric acid levels, a single unit increase in uricemia indicated a CAP increase by 14 dB/m, after adjusting for confounders (coefficient: 14.07, 95%CI 0.6-27.54). Conclusions: Clinical-metabolic screening for NAFLD cannot ignore uricemia, especially in patients with obesity.